Language and communication disorders associated with physiological aging - Chrut, Aneta; Pierzak, Monika; Gorzelak, Martyna; Kasperczuk-Bajda, Agnieszka (Journal of Education, Health and Sport, 2018)
Introduction: In the process of physiological aging leads to changes related to human functioning. Modifications also apply to the sphere of cognitive and related competencies: language and communication. Ability to efficiently use speech and language at the age of senioralnym is important not only because of intellectual functioning, but also serves as pragmatic. Language is in fact an essential tool for building social relationships. The aim of the study was to analysis of the literature on changes in language and communicative competence in the process of physiological aging. Results: With age, the deterioration observed in language and communication skills of older people. In the area of language skills is observed senile changes at all levels of posts: phonological, syntactic and semantic. The elderly are observable phenomenon, which does not notice the earlier stages of life. In the statements of senior citizens should pay particular attention to phenomena such as TOT (tip-of-the-tongue) and OTV (off-target verbosity). Summary: The speech of seniors is a reflection of changes occurring within the cognitive functions of both the basic and the higher ones. Research on the use of language by seniors are an interesting topic for an interdisciplinary group of specialists. In order to delay the aging process in the field of cognitive and linguistic advised to inspire the elderly to educational activity, providing them thus improving the quality of life.